Family as a framing resource for political identity construction: Introduction sequences in presidential primary debates. (25th June 2015) - Sclafani, Jennifer
Abstract This study investigates the construction of political identity in the 2011–2012 US Republican presidential primary debates. Focusing on candidates' self-introductions, I analyze how candidates use references to family members and roles to frame their political identities or 'presidential selves'. Family references are shown to (i) frame candidates' personal identities as family men/women; (ii) interweave the spheres of home and politics and consequently, their private and public selves; (iii) serve as a tool of discursive one-upmanship in self-introduction sequences; and (iv) demonstrate intimate familiarity and expertise on the topic of national security. This study extends research on family discourse and identity by examining the rhetorical function of mentioning family-related identities in explicitly persuasive public discourse, and contributes to sociolinguistic research on political discourse by examining how family identities serve as a resource for framing political identities. (Discourse analysis, framing, family, identity, political discourse, presidential debates, sequentiality)